CXCR2 May Serve as a Useful Index of Disease Activity in Interstitial Lung Disease Associated With Primary Sjögren’s Syndrome - Zhu, Xiaofang; Lu, Saisai; Zhu, Lixia; Yu, Mengjiao; Wei, Tingting; Zhu, Xiaochun; Chen, Dan; Chen, Chengshui (Frontiers in Molecular Biosciences, 2021)
Background: Primary Sjögren’s syndrome (pSS) is a chronic systemic autoimmune disease characterized by typical autoantibody production and lymphocytic-mediated exocrine gland damage. Interstitial lung disease (ILD) is a common complication of pSS and can be associated with a poor prognosis. However, the pathogenesis of ILD in pSS is still unclear. Methods: In this study, we used RNA sequencing to investigate the gene-expression profile of the minor salivary glands (MSGs) from 36 patients with ILD-pSS and 128 patients with non-ILD-pSS. Results: In the remarkably enriched chemokine-mediated signaling pathway, C-X-C motif chemokine receptor 2 (CXCR2), a receptor for interleukin-8, which participates in the activation of neutrophils, was found to be significantly elevated in both MSG and plasma from pSS patients with vs. without ILD (p < 0.001). Furthermore, the CXCR2 expression level in MSG and plasma was significantly associated with the diffusing capacity of the lungs for carbon monoxide, erythrocyte sedimentation rate, and EULAR Sjögren’s Syndrome disease Activity Index in ILD-pSS. Conclusion: Therefore, with its potential role in ILD progression in patients with pSS and its strong association with clinical manifestations of the disease, CXCR2 may serve as a useful index for disease activity in ILD associated with pSS.